Wave Equation for Electromagnetic Radiation

The wave equation for electromagnetic radiation in free space can be derived from Maxwell's equations. It describes how electric and magnetic fields propagate as waves through space. The equations are given by:

2E1c22Et2=0\nabla^2 \mathbf{E} - \frac{1}{c^2} \frac{\partial^2 \mathbf{E}}{\partial t^2} = 0 2B1c22Bt2=0\nabla^2 \mathbf{B} - \frac{1}{c^2} \frac{\partial^2 \mathbf{B}}{\partial t^2} = 0

Here:

  • E\mathbf{E} is the electric field vector.
  • B\mathbf{B} is the magnetic field vector.
  • 2\nabla^2 is the Laplacian operator, which represents the spatial part of the wave equation.
  • cc is the speed of light in a vacuum.
  • 2t2\frac{\partial^2}{\partial t^2} is the second derivative with respect to time.

These equations indicate that both the electric and magnetic fields satisfy the same form of wave equation and propagate at the speed of light cc.

In terms of a scalar field ψ\psi, the wave equation in three-dimensional space is often written as:

2ψ1c22ψt2=0\nabla^2 \psi - \frac{1}{c^2} \frac{\partial^2 \psi}{\partial t^2} = 0

This general form can represent various types of waves, including electromagnetic waves, when ψ\psi is replaced with the corresponding field components.

Electromagnetic Wave Propagation in Free Space

It is not a single video but a playlist, and it contains two videos. When one video finishes, the next will play automatically.

Topic asked in Applied Physics 2023 (CBCS/NEP) question paper Section D - 7(a).

In free space, electromagnetic waves propagate according to Maxwell's equations without any interaction with a material medium. This scenario is fundamental to understanding the behavior of electromagnetic radiation, including light and radio waves.

EM Wave Equations for Free Space in Terms of Electric Field (E)

Gauss's Law for Electricity

E=ρϵ0\nabla \cdot \mathbf{E} = \frac{\rho}{\epsilon_0}

For Free space ρ=0\rho = 0. Therefore:

E=0(i)\nabla \cdot \mathbf{E} = 0 \quad \text{(i)}

Gauss's Law for Magnetism

B=0(ii)\nabla \cdot \mathbf{B} = 0 \quad \text{(ii)}

Faraday's Law of Electromagnetic Induction

×E=Bt(iii)\nabla \times \mathbf{E} = -\frac{\partial \mathbf{B}}{\partial t} \quad \text{(iii)}

Ampère's Law with Maxwell's Correction

×B=μ0ϵ0Et\nabla \times \mathbf{B} = \mu_0 \epsilon_0 \frac{\partial \mathbf{E}}{\partial t}

or

×H=Dt(iv) \nabla \times \mathbf{H} = \frac{\partial \mathbf{D}}{\partial t} \quad \text{(iv)}

Now, taking curl of Eq. (iii)

×(×E)=t(×B)(v)\nabla \times (\nabla \times \mathbf{E}) = -\frac{\partial}{\partial t} (\nabla \times \mathbf{B} ) \quad \text{(v)}

From vector identity, we know:

×(×E)=(E)2E\nabla \times (\nabla \times \mathbf{E}) = \nabla (\nabla \cdot \mathbf{E}) - \nabla^2 \mathbf{E}

From Eq (v):

(E)2E=t(×B)\nabla (\nabla \cdot \mathbf{E}) - \nabla^2 \mathbf{E} = -\frac{\partial}{\partial t} (\nabla \times \mathbf{B} )

Therefore, from Eq. (i) and using B=μH\mathbf{B} = \mu \mathbf{H}

02E=μ0t(×H)0 - \nabla^2 \mathbf{E} = -\mu_0 \frac{\partial}{\partial t} (\nabla \times \mathbf{H})

From Eq. (iv):

2E=μ0tDt\nabla^2 \mathbf{E} = \mu_0 \frac{\partial}{\partial t} \frac{\partial \mathbf{D}}{\partial t}

As D=ϵ0E\mathbf{D} = \epsilon_0 \mathbf{E}, therefore:

2E=μ0ϵ02Dt2(vi)\nabla^2 \mathbf{E} = \mu_0 \epsilon_0 \frac{\partial^2 \mathbf{D}}{\partial t^2} \quad \text{(vi)}

General Wave Expression,

2ψ=1V22ψt2(vii)\nabla^2 \psi = \frac{1}{V^2} \frac{\partial^2 \psi}{\partial t^2} \quad \text{(vii)}

Comparing Eq. (vi) and (vii)

1V2=μ0ϵ0\frac{1}{V^2} = \mu_0 \epsilon_0

or

V=1μ0ϵ0(viii)V = \frac{1}{\sqrt {\mu_0 \epsilon_0}} \quad \text{(viii)}

Multiplying and dividing Eq. (viii) by 4π\sqrt {4 \pi} and we know 14πϵ0=9×109\frac{1}{\sqrt {4 \pi \epsilon_0}} = \sqrt {9 \times 10^9}, μ0=107\mu_0 = 10^{-7}:

V=3×108m/sV = 3 \times 10^8 m/s

EM Wave Equations for Free Space in Terms of Magnetic Field (H)

Gauss's Law for Electricity

E=ρϵ0\nabla \cdot \mathbf{E} = \frac{\rho}{\epsilon_0}

For Free space ρ=0\rho = 0. Therefore:

E=0(i)\nabla \cdot \mathbf{E} = 0 \quad \text{(i)}

Gauss's Law for Magnetism

B=0(ii)\nabla \cdot \mathbf{B} = 0 \quad \text{(ii)}

Faraday's Law of Electromagnetic Induction

×E=Bt(iii)\nabla \times \mathbf{E} = -\frac{\partial \mathbf{B}}{\partial t} \quad \text{(iii)}

Ampère's Law with Maxwell's Correction

×B=μ0ϵ0Et\nabla \times \mathbf{B} = \mu_0 \epsilon_0 \frac{\partial \mathbf{E}}{\partial t}

or

×H=Dt(iv) \nabla \times \mathbf{H} = \frac{\partial \mathbf{D}}{\partial t} \quad \text{(iv)}

Now, taking curl of Eq. (iv)

×(×H)=t(×D)(v)\nabla \times (\nabla \times \mathbf{H}) = \frac{\partial}{\partial t} (\nabla \times \mathbf{D} ) \quad \text{(v)}

From vector identity we know:

×(×H)=(H)2H\nabla \times (\nabla \times \mathbf{H}) = \nabla (\nabla \cdot \mathbf{H}) - \nabla^2 \mathbf{H}

From Eq (v):

(H)2H=t(×D)\nabla (\nabla \cdot \mathbf{H}) - \nabla^2 \mathbf{H} = \frac{\partial}{\partial t} (\nabla \times \mathbf{D} )

Therefore, from Eq. (ii) and using B=μ0H\mathbf{B} = \mu_0 \mathbf{H} and D=ϵ0E\mathbf{D} = \epsilon_0 \mathbf{E}

02H=ϵ0t(×E)0 - \nabla^2 \mathbf{H} = \epsilon_0 \frac{\partial}{\partial t} (\nabla \times \mathbf{E})

From Eq. (iii),

2H=ϵ0t(Bt)-\nabla^2 \mathbf{H} = \epsilon_0 \frac{\partial}{\partial t} (-\frac{\partial \mathbf{B}}{\partial t})

As B=μ0H\mathbf{B} = \mu_0 \mathbf{H} therefore:

2H=μ0ϵ02Ht2(vi)\nabla^2 \mathbf{H} = \mu_0 \epsilon_0 \frac{\partial^2 \mathbf{H}}{\partial t^2} \quad \text{(vi)}

General Wave Expression,

2ψ=1V22ψt2(vii)\nabla^2 \psi = \frac{1}{V^2} \frac{\partial^2 \psi}{\partial t^2} \quad \text{(vii)}

Comparing Eq. (vi) and (vii)

1V2=μ0ϵ0\frac{1}{V^2} = \mu_0 \epsilon_0

or

V=1μ0ϵ0=c(viii)V = \frac{1}{\sqrt {\mu_0 \epsilon_0}} = c \quad \text{(viii)}

Hence velocity of EM wave in free space is equal to speed of light.

Multiplying and dividing Eq. (viii) by 4π\sqrt {4 \pi} and we know 14πϵ0=9×109\frac{1}{\sqrt {4 \pi \epsilon_0}} = \sqrt {9 \times 10^9}, μ0=107\mu_0 = 10^{-7}

V=3×108m/sV = 3 \times 10^8 m/s

Characteristics of Electromagnetic Waves in Free Space

  • Speed of Light: From Maxwell's equations, the speed vv of electromagnetic waves in free space is:v=c3×108m/sv = c \approx 3 \times 10^8 \, \text{m/s}

  • Transverse Nature: Electric and magnetic fields oscillate perpendicular to the direction of propagation.

  • Wave Vector: The wave vector kk indicates the direction of propagation and is related to the wavelength λλ by k=2πλn^\mathbf{k} = \frac{2\pi}{\lambda} \hat{\mathbf{n}} where n^\hat{\mathbf{n}} is the unit vector in the direction of propagation.

Electromagnetic Wave Propagation in Isotropic Dielectric Medium

In an isotropic dielectric medium, electromagnetic waves interact with the medium's atoms and molecules, influencing their propagation characteristics compared to free space. Understanding wave propagation in such mediums is crucial for various applications in optics, telecommunications, and materials science.

Maxwell's Equations in Dielectric Medium

Maxwell's equations describe electromagnetic wave behavior in a dielectric medium:

Gauss's Law for Electricity

E=ρϵ\nabla \cdot \mathbf{E} = \frac{\rho}{\epsilon}

For Free space ρ=0\rho = 0. Therefore:

E=0(i)\nabla \cdot \mathbf{E} = 0 \quad \text{(i)}

Gauss's Law for Magnetism

B=0(ii)\nabla \cdot \mathbf{B} = 0 \quad \text{(ii)}

Faraday's Law of Electromagnetic Induction

×E=Bt(iii)\nabla \times \mathbf{E} = -\frac{\partial \mathbf{B}}{\partial t} \quad \text{(iii)}

Ampère's Law with Maxwell's Correction

×B=μϵEt\nabla \times \mathbf{B} = \mu \epsilon \frac{\partial \mathbf{E}}{\partial t}

or

×H=Dt(iv) \nabla \times \mathbf{H} = \frac{\partial \mathbf{D}}{\partial t} \quad \text{(iv)}

Now, taking curl of Eq. (iii)

×(×E)=t(×B)(v)\nabla \times (\nabla \times \mathbf{E}) = -\frac{\partial}{\partial t} (\nabla \times \mathbf{B} ) \quad \text{(v)}

From vector identity we know:

×(×E)=(E)2E\nabla \times (\nabla \times \mathbf{E}) = \nabla (\nabla \cdot \mathbf{E}) - \nabla^2 \mathbf{E}

From Eq (v):

(E)2E=t(×B)\nabla (\nabla \cdot \mathbf{E}) - \nabla^2 \mathbf{E} = -\frac{\partial}{\partial t} (\nabla \times \mathbf{B} )

Therefore, from Eq. (i) and using B=μH\mathbf{B} = \mu \mathbf{H}

02E=μt(×H)0 - \nabla^2 \mathbf{E} = -\mu \frac{\partial}{\partial t} (\nabla \times \mathbf{H})

From Eq. (iv):

2E=μtDt\nabla^2 \mathbf{E} = \mu \frac{\partial}{\partial t} \frac{\partial \mathbf{D}}{\partial t}

As D=ϵE\mathbf{D} = \epsilon \mathbf{E}, therefore:

2E=μϵ2Dt2(vi)\nabla^2 \mathbf{E} = \mu \epsilon \frac{\partial^2 \mathbf{D}}{\partial t^2} \quad \text{(vi)}

General Wave Expression:

2ψ=1V22ψt2(vii)\nabla^2 \psi = \frac{1}{V^2} \frac{\partial^2 \psi}{\partial t^2} \quad \text{(vii)}

Comparing Eq. (vi) and (vii)

1V2=μϵ\frac{1}{V^2} = \mu \epsilon

or

V=1μϵV = \frac{1}{\sqrt {\mu \epsilon}}

Eq. (viii) shows that the propagation velocity of an electromagnetic wave in a dielectric medium is less than that in free space.

For a dielectric medium with relative permittivity ϵr\epsilon_r and relative permeability μr\mu_r:

V=cμrϵrV = \frac{c}{\sqrt {\mu_r \epsilon_r}}

where c=1μ0ϵ0 c = \frac{1}{\sqrt {\mu_0 \epsilon_0}}

In non-magnetic dielectric media, μr1\mu_r \approx 1, so:

V=cμrV = \frac{c}{\sqrt {\mu_r}}

Hence,

Thus, the refractive index nn = Relative permittivity    \sqrt {\text{Relative permittivity}} \; \; or     n=ϵr\; \; n = \sqrt {\epsilon_r}

Characteristics of Electromagnetic Waves in Dielectric Medium

  • Speed of Light: In a dielectric medium, the speed vv of electromagnetic waves is: v=cϵrv = \frac{c}{\sqrt{\epsilon_r}}, where ϵr\epsilon_r is the relative permittivity of the medium.

  • Wave Vector: The wavelength λ\lambda in the medium is related to the wavelength in a vacuum λ0\lambda_0 by: λ=λ0n\lambda = \frac{\lambda_0}{n} where nn is the refractive index of the medium.

  • Wave Polarization: The interaction of electromagnetic waves with the dielectric medium can lead to effects like refraction, reflection, and absorption. Polarization of the wave may affect these interactions.

Poynting Vector and Poynting Theorem

It is not a single video but a playlist, and it contains five videos. When one video finishes, the next will play automatically.

Please click on Watch on YouTube button if you see Video unavailable error.

Topic asked in Applied Physics 2023 (CBCS/NEP) question paper Section E (Compulsory) - 9(d).

Electromagnetic waves carry energy as they propagate through space. This energy is associated with both the electric and magnetic fields. The amount of energy flowing through a unit area, perpendicular to the direction of energy propagation per unit time, is called the Poynting vector, denoted by S\mathbf{S} . Mathematically it is defined:

S=1μ0E×B\mathbf{S} = \frac{1}{\mu_0} \mathbf{E} \times \mathbf{B}

In free space, where D=ϵ0E\mathbf{D} = \epsilon_0 \mathbf{E} and B=μ0H\mathbf{B} = \mu_0 \mathbf{H}, the Poynting vector can be expressed as:

S=E×H\mathbf{S} = \mathbf{E} \times \mathbf{H}

where E\mathbf{E} and H\mathbf{H} represent the instantaneous values of the electric and magnetic field vectors. The Poynting vector S\mathbf{S} is perpendicular to both E\mathbf{E} and H\mathbf{H}, and points in the direction of wave propagation. Its units are watts per square meter W/m2W/m^2, representing the rate of energy transport per unit area.

The Poynting theorem is a fundamental principle in electromagnetism that describes the conservation of energy for electromagnetic fields. It provides a relationship between the power flowing through a surface and the rate of change of electromagnetic energy within a volume. This theorem is named after the physicist John Henry Poynting.

The Poynting theorem states that the rate at which electromagnetic energy is transferred through a surface is equal to the negative rate of change of electromagnetic energy stored in the volume enclosed by that surface, plus the work done by external forces (if any).

Mathematically, the theorem can be expressed as:

VEJdV=t[V(12μH2+12ϵE2)dV]\int_V \vec{E} \cdot \vec{J} \, dV = \frac{\partial}{\partial t} \left[ \int_V \left( \frac{1}{2} \mu H^2 + \frac{1}{2} \epsilon E^2 \right) dV \right]
S(E×H)dS- \oint_S (\vec{E} \times \vec{H}) \cdot d \vec{S}

where:

  • EE is the electric field vector.
  • HH is the magnetic field vector.
  • JJ is the current density vector.
  • DD is the electric displacement field vector, where D=ϵED = \epsilon E.
  • BB is the magnetic flux density vector, where B=μHB = \mu H.
  • t\frac{\partial}{\partial t} represents the time derivative.
  • S(E×H)dS\oint_S (E \times H ) \cdot dS is the integral of the Poynting vector across a closed surface SS.

Derivation

We can calculate the energy density carried by electromagnetic waves with the help of Maxwell's equations given below.

×D=0(i) \nabla \times \vec{D} = 0 \quad \text{(i)} ×B=0(ii)\nabla \times \vec{B} = 0 \quad \text{(ii)} ×E=Bt(iii) \nabla \times \vec{E} = -\frac{\partial \vec{B}}{ \partial t} \quad \text{(iii)} ×H=J+Dt(iv) \nabla \times \vec{H} = \vec{J} + \frac{\partial \vec{D}}{\partial t} \quad \text{(iv)}

Take scalar (dot) product of Eq. (iii) and Eq. (iv) with H\vec{H} and E\vec{E} respectively, i.e.,

H(×E)=HBt(v) \vec{H} \cdot (\nabla \times \vec{E}) = -\vec{H} \cdot \frac{\partial \vec{B}}{\partial t} \quad \text{(v)} E(×H)=EJ+EDt(vi) \vec{E} \cdot (\nabla \times \vec{H}) = \vec{E} \cdot \vec{J} + \vec{E} \cdot \frac{\partial \vec{D}}{\partial t} \quad \text{(vi)}

Subtract Eq. (v) from Eq. (vi), i.e.,

H(×E)E(×H)= \vec{H} \cdot (\nabla \times \vec{E}) - \vec{E} \cdot (\nabla \times \vec{H}) =
HBtEJEDt-\vec{H} \cdot \frac{\partial \vec{B}}{\partial t} - \vec{E} \cdot \vec{J} - \vec{E} \cdot \frac{\partial \vec{D}}{\partial t}
=(HBt+EDt)EJ = -\left( \vec{H} \cdot \frac{\partial \vec{B}}{\partial t} + \vec{E} \cdot \frac{\partial \vec{D}}{\partial t} \right) - \vec{E} \cdot \vec{J}

or

div(E×H)=(HBt+EDt)div(\vec{E} \times \vec{H}) = -\left( \vec{H} \cdot \frac{\partial \vec{B}}{\partial t} + \vec{E} \cdot \frac{\partial \vec{D}}{\partial t} \right)
EJ(vii)- \vec{E} \cdot \vec{J} \quad \text{(vii)}
[div(A×B)=BcurlAAcurlB][ \text{div} (\vec{A} \times \vec{B}) = \vec{B} \cdot \text{curl} \vec{A} - \vec{A} \cdot \text{curl} \vec{B} ]

Using the relations B=μH\vec{B} = \mu \vec{H} and D=ϵE\vec{D} = \epsilon \vec{E}, we can get

EDt=Et(ϵE)=12t(E2)= \vec{E} \cdot \frac{\partial \vec{D}}{\partial t} = \vec{E} \cdot \frac{\partial}{\partial t} (\epsilon \vec{E}) = \frac{1}{2} \frac{\partial}{\partial t} (E^2) = t(12ED)[E2=EE]\frac{\partial}{\partial t} \left( \frac{1}{2} \vec{E} \cdot \vec{D} \right) \quad [E^2 = \vec{E} \cdot \vec{E}]

HBt=Ht(μH)=12μt(H2)=\vec{H} \cdot \frac{\partial \vec{B}}{\partial t} = \vec{H} \cdot \frac{\partial}{\partial t} (\mu \vec{H}) = \frac{1}{2} \mu \frac{\partial}{\partial t} (H^2) =

t(12HB)[H2=HH] \frac{\partial}{\partial t} \left( \frac{1}{2} \vec{H} \cdot \vec{B} \right) \quad [H^2 = \vec{H} \cdot \vec{H}]

Now Eq. (vii) can be written as

div(E×H)=t[12(HB+ED)]EJdiv(\vec{E} \times \vec{H}) = \frac{\partial}{\partial t} \left[ \frac{1}{2} (\vec{H} \cdot \vec{B} + \vec{E} \cdot \vec{D}) \right] - \vec{E} \cdot \vec{J}

or

EJ=t[12(HB+ED)] \vec{E} \cdot \vec{J} = \frac{\partial}{\partial t} \left[ \frac{1}{2} (\vec{H} \cdot \vec{B} + \vec{E} \cdot \vec{D}) \right] div(E×H)(viii)- \text{div} (\vec{E} \times \vec{H}) \quad \text{(viii)}

Integrating Eq. (viii) over a volume VV enclosed by a surface SS, we get

VEJdV=V[t(12(HB+ED))]dV\int_V \vec{E} \cdot \vec{J} \, dV = \int_V \left[ \frac{\partial}{\partial t} \left( \frac{1}{2} (\vec{H} \cdot \vec{B} + \vec{E} \cdot \vec{D}) \right) \right] dV

Vdiv(E×H)dV- \int_V \text{div} (\vec{E} \times \vec{H}) \, dV or

VEJdV=t[V(12μH2+12ϵE2)dV]\int_V \vec{E} \cdot \vec{J} \, dV = \frac{\partial}{\partial t} \left[ \int_V \left( \frac{1}{2} \mu H^2 + \frac{1}{2} \epsilon E^2 \right) dV \right]

S(E×H)dS(ix) - \oint_S (\vec{E} \times \vec{H}) \cdot d \vec{S} \quad \text{(ix)}

[B=μH,D=ϵE][\vec{B} = \mu \vec{H}, \, \vec{D} = \epsilon \vec{E}]

and

Vdiv(E×H)dV=S(E×H)dS(x)\int_V \text{div} (\vec{E} \times \vec{H}) \, dV = \oint_S (\vec{E} \times \vec{H}) \cdot d \vec{S} \quad \text{(x)}

Eq. (ix) can also be written as

VEJdV=t[V(12μH2+12ϵE2)dV]\int_V \vec{E} \cdot \vec{J} \, dV = \frac{\partial}{\partial t} \left[ \int_V \left( \frac{1}{2} \mu H^2 + \frac{1}{2} \epsilon E^2 \right) dV \right]

S(E×H)dS- \oint_S (\vec{E} \times \vec{H}) \cdot d \vec{S}

Interpretation

(a) v(EJ)dV\int_v (\mathbf{E} \cdot \mathbf{J}) dV : Represents the total power dissipated in the volume VV due to the motion of charges.

(b) tv[12μH2+12ϵE2]dV\frac{\partial}{\partial t} \int_v \left[ \frac{1}{2} \mu H^2 + \frac{1}{2} \epsilon E^2 \right] dV : Represents the rate of change of energy stored in the electric and magnetic fields within volume volume VV.

(c) s(E×H)dS\int_s (\mathbf{E} \times \mathbf{H}) \cdot d\mathbf{S} : Represents the rate of energy flow (power) through the surface SS, i.e., the net power flowing out of volume VV. The vector S=E×HS = E \times H is known as the Poynting vector.

The equation (x) derived is known as the Poynting theorem, which describes the conservation of energy for electromagnetic fields. It states that the power transferred into the field is equal to the sum of the rate of change of electromagnetic energy within a volume and the rate of energy flow out through the boundary surface. This represents the energy conservation law in electromagnetism.

References: Engineering Physics, H.K Malik & A.K Singh, Tata McGraw-Hill , Technical Physics

How's article quality?

Last updated on -

Page Contents